Zambia Climate-Smart Agriculture Investment Plan : Analyses to Support the Climate-Smart Development of Zambia’s Agriculture Sector - World Bank (World Bank, Washington, DC, 2019)
Zambia’s agricultural sector represents the backbone of its rural economy and holds great potential for the entire country. Zambia’s agriculture sector faces challenges and is likely to grow more vulnerable as a result of climate change and risk. At the same time, land use, land-use change and forestry (LULUCF), and agriculture sector account for approximately 93 percent of the country’s carbon footprint. The Government of the Republic of Zambia (GoZ) is integrating climate change concerns into its agriculture policy agenda. Under its Zambia climate-smart agriculture (CSA) strategy framework, the GoZ is promoting the rollout of CSA practices that will sustainably increase productivity, enhance resilience, and reduce or remove greenhouse gas (GHG) emissions. The CSA investment plan (CSAIP) aims to identify and fill knowledge gaps about CSA’s local- and national-level benefits, specifically under climate change, inform policy development, and prioritize investment opportunities. The World Bank collaborated with the GoZ to develop a CSAIP intended to support the operationalization of the country’s climate commitments toward development of a productive, resilient, and low-emission agriculture sector. The CSAIP development began with a participatory process that identified the agriculture sector’s policy goals. This report takes the next step by assessing the impacts of a suite of CSA practices on achieving the sector goals and on household welfare. The report concludes with recommendations and proposals for future CSA investments.